Origin of Oil Seeps in West Sulawesi Onshore, Indonesia: Geochemical Constraints and Paleogeographic Reconstruction of the Source Facies - Sutadiwiria, Yarra; Yeftamikha, .; Hamdani, Ahmad Helman; Andriana, Yoga; Haryanto, Iyan; Sunardi, Edy (Faculty of Geological Engineering, Universitas Padjadjaran, 2017)
ABSTRACTNumerous oil and gas seeps occur at onshore West and South Sulawesi. These may indicate the presence of active petroleum system in subsurface hence the area is worthy for further exploration. No discovery well so far in this area. Therefore, the seeps provide significant data to build integrated petroleum system analysis.A number of geochemical analysis were conducted on the oil seeps and rock samples from outcrop and well cuttings to reveal the source rocks that generate the oils. Triterpane m/z 191 shows low content of tricyclic terpane, low norhopane to hopane, and abundant oleanane. Sterane m/z 217 and bicyclic alkane m/z 123 show dominant C29 sterane and bicadinane. These biomarkers indicate that the source of oils are coals and/or coaly shales deposited in fluvio-deltaic setting. Contribution from marine input is shown in Karama region to the south.Based on stratigraphic setting of West and South Sulawesi, the best candidate for the source of oil seeps is Eocene coals or coaly shales of Toraja or Kalumpang Formation. The Eocene coal samples have been characterized and show similar GC alkane distribution with the oil seeps. Contribution from marine facies, which may age-equivalent to these coals are shown in Karama region.Aromatic methyl phenanthrene m/z 178 and m/z 192 were also analyzed to know their maturities and they were generated at maturity level equivalent with Ro 0.8-1.0 %.Based on geochemical constraints and geologic data, a paleogeographic setting of Eocene Toraja/Kalumpang Formation was built to know better about the paleo-source facies of the oils and its geochemical characteristics. Keywords: Biomarker, coaly shales, Toraja/Kalumpang Formation